A Study on Manner of Spending Leisure Time among Citizens of Ahwaz - masoumeh bagheri; sajjad bahmaee (توسعه اجتماعی)
Check leisure citizens, due to changes in lifestyle and tastes of modern man is of interest to sociologists. This study aim to gain awareness of how people spend their leisure time in Ahwaz done. The data collected by all citizens in Ahvaz time constraints and financial problems, it was impossible. After calculating the sample size, the citizens of the city of Ahvaz, 400 randomly selected as a sample, and the data were collected.